The comparison of students' academic stress in biology class at public and private high schools - Salsabila, Azura; Saputri, Nova Vivi Clara; Rohimah, Tina Rizqiyati; Rahmat, Adi (Universitas Islam Negeri Sumatera Utara, 2023)
Students are demanded by school assignments, and many of them feel under pressure when learning biology. This situation is a trigger for academic stress which has an impact on student achievement. This study aims to identify and compare the factors that influence academic stress on students studying biology at the senior high school level. The research method used was an ex post facto survey using a sample of 54 students with an age range between 16-18 years. Data were obtained through a questionnaire with 9 scales of answer choices and interviews. The results showed that the level of preference for biology subjects for both public and private high school students was quite good, but most students experienced academic stress with a fairly high category in terms of motivation, self-confidence, the education system, teachers, and school conditions. This research implies that teachers are expected to create learning strategies by paying attention to the psychological conditions of students so that student learning outcomes can be maximized.